Tuning the interactions between electron spins in fullerene-based triad systems - Lebedeva, Maria A.; Chamberlain, Thomas W.; Davies, E. Stephen; Thomas, Bradley E.; Schröder, Martin; Khlobystov, Andrei N. (Beilstein-Institut, 2014)
A series of six fullerene-linker-fullerene triads have been prepared by the stepwise addition of the fullerene cages to bridging moieties thus allowing the systematic variation of fullerene cage (C60 or C70) and linker (oxalate or terephthalate) and enabling precise control over the inter-fullerene separation. The fullerene triads exhibit good solubility in common organic solvents, have linear geometries and are diastereomerically pure. Cyclic voltammetric measurements demonstrate the excellent electron accepting capacity of all triads, with up to 6 electrons taken up per molecule in the potential range between -2.3 and 0.2 V (vs. Fc+/Fc). No significant electronic interactions between fullerene cages are observed in the ground state indicating that the individual properties of each C60 or C70 cage are retained within the triads. The electron-electron interactions in the electrochemically generated dianions of these triads, with one electron per fullerene cage were studied by EPR spectroscopy. The nature of electron-electron coupling observed at 77 K can be described as an equilibrium between a doublet and triplet state biradical which depends on the interfullerene spacing. The shorter oxalate-bridged triads exhibit stronger spin-spin coupling with triplet character, while in the longer terephthalate-bridged triads the intramolecular spin-spin coupling is significantly reduced.